Neural and behavioural correlates of autobiographical memory retrieval in patients with major depressive disorder and a history of trauma exposure. (February 2018) - Parlar, Melissa; Densmore, Maria; Hall, Geoffrey B.C.; Lanius, Ruth; McKinnon, Margaret C.
Abstract: Alterations in autobiographical memory (AM) performance have been identified in major depressive disorder (MDD) and in trauma-related disorders, however, the neural and behavioural correlates of AM retrieval in patients with MDD and a co-morbid history of trauma remain unexplored. Here, we used behavioural and neuroimaging techniques to investigate AM in this patient group and in matched healthy comparison subjects (HCs). Twenty patients with MDD and trauma exposure and 20 HCs underwent fMRI scanning while recalling positive, negative, and neutral events. Participants were subsequently administered the Autobiographical Interview (Levine et al., 2002), allowing for separation of episodic and non-episodic details of memories. Key clinical variables, including illness severity, dissociative (e.g., depersonalization, derealization) symptoms, and history of parental bonding, were assessed. Compared to controls, patients showed reduced activation in the left parahippocampus and left anterior insula during retrieval of positive memories. Among patients, greater specificity of positive AM recall on the Autobiographical Interview was related to reduced activation of the left anterior insula during retrieval of positive memories. Moreover, increased left parahippocampal activation during negative memory recall was related to heightened levels of paternal care among the patient group. Taken together, these findings point towards potential alterations in key neural processes (e.g., episodic vividness and embodiment) associated with AM retrieval among MDD patients with a history of co-morbid trauma exposure. These alterations appear unrelated to illness severity, but instead are associated with parental bonding. Highlights: Patients and controls differ in their neural correlates of positive memory recall. Patients show less activation in the left hippocampus and left anterior insula. Behavioural memory performance is related to neural correlates of memory recall. Neural correlates of memory recall are related to self-reported paternal care.